2012
DOI: 10.5152/akd.2013.039
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level is an independent risk factor for presence of calcium in coronary arteries: an observational case-controlled study

Abstract: Objective: A link between uric acid levels and cardiovascular diseases has been previously reported. Coronary artery calcium score (CACS) is a marker of atherosclerotic disease and a predictor of cardiovascular events. We sought to determine if serum uric acid level is an independent risk factor for the presence of calcium in coronary arteries. Methods: Four hundred and forty-two patients who were evaluated in the cardiology outpatient clinic for suspected coronary heart disease with a low-moderate risk for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 35 publications
(42 reference statements)
0
34
0
3
Order By: Relevance
“…Clinical research has also shown that correlations between the higher serum uric acid levels and calcification of the coronary artery [17], the decreased flow-mediated dilation, which indicates the vascular endothelial function [18] and higher pulse wave velocity [19], suggest that hyperuricemia is associated with arteriosclerosis. It is almost certain that hyperuricemia induces arteriosclerosis and hypertension.…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 99%
“…Clinical research has also shown that correlations between the higher serum uric acid levels and calcification of the coronary artery [17], the decreased flow-mediated dilation, which indicates the vascular endothelial function [18] and higher pulse wave velocity [19], suggest that hyperuricemia is associated with arteriosclerosis. It is almost certain that hyperuricemia induces arteriosclerosis and hypertension.…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 99%
“…The average age of participants ranged from 36.5 to 84.5 . There are one case control, three cohorts, and seven cross‐sectional studies in total. Of these studies, nine included both genders, one included only men, and one included only women .…”
Section: Resultsmentioning
confidence: 99%
“…Three cohort studies reported the association between hyperuricemia and CAC progression. All of the selected studies were assessed as high quality according to the NOS scale (10 studies have NOS scores as 9 and 1 study as 8). See Table .…”
Section: Resultsmentioning
confidence: 99%
“…Serum UA was found to be an independent risk factor for the presence of CAC in a group of 442 patients who were evaluated for suspected CHD …”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated a relationship between serum UA levels and CAC score, but other studies do not support these findings …”
mentioning
confidence: 88%